2002
DOI: 10.1002/jctb.606
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of palladium by Desulfovibrio desulfuricans

Abstract: Palladium uptake by resting cell suspensions of Desulfovibrio desulfuricans NCIMB 8307 was studied without or with electron donor (formate), which gave metal uptake attributable to biosorption of Pd(II) and bioreduction of Pd(II) to Pd(0), respectively. The maximum biosorption capacity of palladium (at pH 2) was up to 196 mg Pd g À1 dry cells (1.85 mmol g À1 ; approx 20% of the dry weight). Biosorption was to 85% of the maximum in less than 10 min and the biomass was saturated within 30 min. Biosorption of Pd(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 24 publications
3
102
0
1
Order By: Relevance
“…2 supplemented with 0.4% (w/v) sodium fumarate and 0.5% (v/v) glycerol. Desulfovibrio desulfuricans NCIMB 8307 was cultured anaerobically in Postgate C medium at 30 o C (Yong et al 2002;.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 supplemented with 0.4% (w/v) sodium fumarate and 0.5% (v/v) glycerol. Desulfovibrio desulfuricans NCIMB 8307 was cultured anaerobically in Postgate C medium at 30 o C (Yong et al 2002;.…”
Section: Methodsmentioning
confidence: 99%
“…The suspension was left for 2 h to allow biosorption of metal (much of the hydrogenase activity was retained for this duration: I. Mikheenko, unpublished) then H 2 was bubbled through the solution for ~30 min. Complete Pd(II) reduction was confirmed as previously described (Yong et al 2002) after the resulting black precipitate settled under gravity.…”
Section: Bio-deposition Of Pd(0) and Precious Metals (Pm)mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common methods for preparing all of these nanoparticles are wet-chemical an aqueous or soil sample onto the organism itself, such as on the cell wall, and does not require the input of energy. Certain bacteria, fungi and plants express peptides or have a modified cell wall which binds to metal ions, and these are able to form stable complexes in the form of nanoparticles [21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that challenging bacteria with oxidised metal species resulted in the precipitation of solid phases of the metal. In the case of precious metals and gold, several studies showed that sulfate-reducing bacteria (SRB) and Fe(III) reducing bacteria are able to reduce palladium (Pd), platinum (Pt) and gold (Au) to the zerovalent form of the metal (Lloyd et al, 1998;Kashefi et al, 2001;Yong et al, 2002a). Bioreduction is a system involving enzymatically-assisted metal precipitation from a high valence to a zerovalent state.…”
mentioning
confidence: 99%